Umowy międzynarodowe jako źródło prawa Unii Europejskiej - Cieśliński, Aleksander (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2017)
European Union is known for a very active participation in international relations with special emphasize put on international agreements being concluded with 3rd states. According to well established case-law EU should respect international law in the exercise of its powers although not automatically but under the condition of protection of fundamental rights. As far as international agreements are concerned under art. 2161 TFEU Union may conclude them with third countries or international organisations where the Treaties so provide or where it is necessary in order to achieveone of the objectives referred to in the Treaties, or is provided for in a legally binding Union act or is likely to affect common rules or alter their scope. According to art. 21811 the opinion of the Court of Justice may be obtained as to whether an agreement envisaged is compatible with Treaties and where it is adverse, the agreement envisaged may not enter into force unless it is amended or the Treaties are revised.It is not the only important function of the CJEU in this area as international agreements of the Union are recognized as acts of the institutions in terms of art. 267 TFUE. Consequently domestic courts may refer to the CJEU in order to receive preliminary rulings concerning their interpretation. Case-law left no doubt that Union’s international agreements are recognized as integral part of its legal order – superior to secondary law but not as a part of primary law. Thanks to that both legislative acts of EU and Member States can be challenged in case of breach of their provisions especially that principle of primacy over domestic law is to be followed here along with direct effect.
Keywords: Unia Europejska; umowy międzynarodowe; kompetencje do zawierania umów międzynarodowych; stosunki UE z państwami trzecimi